Governance in Areas of Limited Statehood: The NGOization of Palestine - Arda, Lama; Banerjee, Subhabrata Bobby (Business & society, 2021)
In this article, we examine the shifting roles played by non-state actors in governing areas of limited statehood. In particular, we focus on the emergence of voluntary grassroots organizations in Palestine and describe how regimes of international development aid transformed these organizations into professional nongovernmental organizations (NGOs) that created new forms of colonial control. Based on in-depth interviews with 145 NGO members and key stakeholders and a historical analysis of limited statehood in Palestine, we found that social relations became disembedded from the local context and re-embedded in new relations with international donor organizations resulting in a depoliticized public sphere. NGOization of the economy also resulted in new forms of exclusion and inclusion as well as contestations between a new class of urban middle-class professionals working in NGOs and the older generation of activists who were involved in grassroots organizations. Our findings have implications for business and human rights and governance in areas of limited statehood, in particular how private actors such as NGOs are able to exercise power in the economy.